Prevalence of Echinococcus Granulosus in Different Intermediate Hosts in Duhok Province, Kurdistan Region, Iraq. - Meerkhan, Azad A.; Mero, Wijdan M.S. (Science Journal of University of Zakho, 2018)
This study was carried out in Duhok provinces, Kurdistan Region/ Iraq from August; 2014 to December 2015.The study focused on the prevalence of CE in slaughtered animals. The total prevalence was 5.25% (11753/223436), with a high rate in sheep (4.25%), and low rates in goats and cattle (0.64% and 0.37%, respectively). With respect to abattoirs involved in the study, the highest prevalence was detected in Akre abattoir (8.21%) and the lowest in Amedy abattoir (4.09%). Among the infected animals, sheep in Akre abattoir recorded the highest prevalence, while cattle in Duhok abattoir recorded the lowest prevalence (7.57 and 0.1%, respectively). Males of sheep, goats and cattle showed higher prevalence (70.51, 63.62, and 92.06%, respectively). Regarding organ involvements, malesand females of cattle showed high liver involvement (63.13 and 84.62%, respectively), while males and females of sheep (62.21 and 60.31%, respectively) and goats (60.59 and 54.51%, respectively) showed high lungs involvements.